Studies on Gastrointestinal Nematodosis and Associated Risk Factors in Dairy Animals of Arid Western Plains of Rajasthan - Panwar, Praveen; Gupta, Abhishek; Choudhary, Poonam; Pilania, P. K. (International Journal of Bio-resource and Stress Management, 2018)
A total of 617 faecal samples (including 235, 188 and 194 samples from native cows, crossbred cows and buffaloes, respectively) were examined from January 2017 to December 2017, with an overall prevalence rate of 56.73% (native: 60.85%, crossbred: 57.45% and buffaloes: 51.03%) for gastrointestinal nematode infections and mixed infection in 11.35% with no statistical difference (p>0.05). Throughout the whole study period strongyles were found to be the most dominant (47.49%) followed by Strongyloides sp. (16.86%). A highly significant statistical variation (p<0.05) were reported in season wise as well as district wise analysis with maximum infection in rainy season (64.90%) and in Jodhpur district (62.54%), respectively. Quantitative analysis revealed EPG (eggs per gram of faeces) for stongyles ranging from 100-2500 (1291±237.56) and Strongyloides sp. from 100-800 (416.67±75.71). Multivariate binary logistic regression model revealed positive association of rainy (B=0.407) and negative association of summer season (B=-.221) when compared to winter season whereas, association was reported negative in Barmer district (B=0.517) when compared to Jodhpur district. Similarly, comparing to native animals, a negative association in crossbred (B=-0.197) and buffaloes (B=-0.462)was also reported in the study period. Coproculture analysis revealed the presence of nematodes of genera Haemonchus sp. (40.58%), Oesophagostomum sp. (26.09%), Strongyloides sp. (18.84%), Trichostrongylus sp. (8.695%) and Cooperia sp. (5.797%) in decreasing order of prevalence. Considering the impact of the infections on animal production and public health, the current investigation may be used to design rational, economic, selectively effective strategic and locally sustainable control programs against gastrointestinal nematode infections in the dairy animals of arid western plains of Rajasthan.